Study of magnetic relaxation, memory and rejuvenation effects in the cluster spin-glass phase of B-site disordered Ca(Fe1/2Nb1/2)O3 perovskite: Experimental evidence for hierarchical model - Kumar A.; Pandey D. (My University, 2025)
We explore the characteristics of the spin-glass phase of the lead-free complex perovskite Ca(Fe1/2Nb1/2)O3 (CFN) below the spin-glass transition temperature TSG ~24 K. The temperature dependence of the coercive field (Hc) and remanent magnetization (Mr) follow exponential behaviour as expected for the glassy phase. Detailed magnetic relaxation measurements as a function of time (t) with temperature (T) cycling on zero-field cooled (ZFC) and field cooled (FC) samples reveal that the cluster spin-glass phase of CFN exhibits a very slow non-exponential decay of thermoremanent magnetization with time as well as memory and rejuvenation effects. Our results demonstrate that the observed memory and rejuvenation effects in the cluster spin-glass phase of CFN can be explained by hierarchical model only and not by the droplet model. © 2020 Elsevier B.V.